Tidal mixing processes amid small‐scale, deep‐ocean topography. Issue 2 (30th January 2015) - Dale, Andrew C.; Inall, Mark E.
Abstract: The nature of tide‐topography interaction reflects the topographic scales experienced by water parcels during their tidal excursions. In the deep ocean these scales are typically subkilometer, yet direct observations of tidal processes on such scales are lacking. At one site, a saddle amid steep and complex Mid‐Atlantic Ridge topography, observations reveal tidally pulsed, bottom‐trapped fronts, overflows, and lee waves in response to a tide combined with a mean flow of similar amplitude. The tidal pulsing of the fronts and overflows was only evident locally, and their phase became unpredictable over scales of hundreds of meters. Enhanced turbulence in a 100–200 m thick bottom boundary layer had an estimated dissipation rate of 2.6 × 10 −2  W m −2, exceeding the large‐scale average of tidal dissipation in mid‐ocean ridge environments but by less than an order of magnitude. This site was not a dissipation "hotspot, " and the processes observed could provide widely distributed mixing to the meridional overturning circulation. Key Points: Tidal processes in the deep ocean reflect subkilometer topographic scales Observations at these scales reveal tidally pulsed overflows and lee waves Dissipation levels suggest a widely distributed mixing contribution to the MOC